Praktyka funkcjonowania Krajowego Ośrodka Zapobiegania Zachowaniom Dyssocjalnym. Uwagi na tle wyroku Trybunału Konstytucyjnego z 23 listopada 2016 roku w sprawie K 6/14 — część II - Kukliński, Patryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The following text continues the considerations made in the author’s article, which appeared in volume 35 of the journal. This text analyses selected current problems connected to the functioning of the National Centre for the Prevention of Antisocial Behaviour in Gostynin, which was established in 2014. The point of reference for author’s deliberations is the judgment of the Polish Constitutional Court (case no. K 6/14). The author, from the perspective of over seven years of the law’s application and in relation to the arguments of the court, analyses problems related to distance requirement of post-penal detention from criminal penalty, as well as the position and role of judges and experts in the process of law application. He also refers to the hunger strike of the National Centre patients, which became an expression of opposition to numerous unresolved problems. Both articles lead to two basic conclusions. Firstly, they prove that the introduced regulation is extremely ineffective. Secondly, they indicate that it is contrary to the standards of human freedoms and rights protection.
Keywords: post-penal detention; dangerous perpetrators; deprivation of liberty; National Centre for the Prevention of Antisocial Behaviour; the judgment of the Polish Constitutional Court from 23 November 2016, case no. K 6/14